1992
DOI: 10.1126/science.1736360
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Phylogenetics: Generation of a Known Phylogeny

Abstract: Although methods of phylogenetic estimation are used routinely in comparative biology, direct tests of these methods are hampered by the lack of known phylogenies. Here a system based on serial propagation of bacteriophage T7 in the presence of a mutagen was used to create the first completely known phylogeny. Restriction-site maps of the terminal lineages were used to infer the evolutionary history of the experimental lines for comparison to the known history and actual ancestors. The five methods used to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
166
1
6

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(174 citation statements)
references
References 9 publications
1
166
1
6
Order By: Relevance
“…In the case of the latter, at least, there may be a "true" phylogeny that accurately depicts the historical patterns of ancestry connecting eukaryote branches to their common root, but the shape of the tree is far from resolved (Baldauf 2003). In fact, except in rare instances where the pattern of evolutionary branching is created in the laboratory and observed directly as it occurs (e.g., Hillis et al 1992;Sanson et al 2002), it is impossible to know with certainty that any given phylogeny is historically accurate. As a result, any reconstructed phylogenetic tree is a hypothesis about relationships and patterns of branching and thus is subject to further testing and revision with the analysis of additional data.…”
Section: The Basics Of Phylogenetic Literacymentioning
confidence: 99%
“…In the case of the latter, at least, there may be a "true" phylogeny that accurately depicts the historical patterns of ancestry connecting eukaryote branches to their common root, but the shape of the tree is far from resolved (Baldauf 2003). In fact, except in rare instances where the pattern of evolutionary branching is created in the laboratory and observed directly as it occurs (e.g., Hillis et al 1992;Sanson et al 2002), it is impossible to know with certainty that any given phylogeny is historically accurate. As a result, any reconstructed phylogenetic tree is a hypothesis about relationships and patterns of branching and thus is subject to further testing and revision with the analysis of additional data.…”
Section: The Basics Of Phylogenetic Literacymentioning
confidence: 99%
“…This expectation is based on results of simulation and experimental studies that have shown most methods tend to estimate phylogeny accurately (28)(29)(30)(31). This is true except when the number of sites sampled is small (32) or the dataset causes inconsistency (33)(34)(35)(36).…”
mentioning
confidence: 99%
“…Viruses are now been used as models for evolutionary biology in experimental evolutionary work, since empirically generated known molecular phylogenies of viruses have the potential to enhance inferential methodology (Hillis et al 1992). Moreover, given the speed of some viral populational processes and technical convenience (millions of individual viruses replicating very fast in milliliter-sized flasks), several aspects of classical evolutionary models are being tested by using viruses (Burch & Chao 1999).…”
Section: What Can We Learn From the Molecular Genetics Of Virusesmentioning
confidence: 99%